Psychological Well-Being and Quality of Life of Breast Cancer Survivors in Negros Occidental - Quiquiles, Carina Christine C.; Medez, Sharon Rose G. (Technium Social Sciences Journal, 2022)
A happy existence is the goal of psychological well-being. It is the result of feeling well and doing well. Quality of life entails developing one’s potential, having some influence over one’s life, overcoming their most challenging battles, and having a feeling of purpose. Hence, this paper described the psychological well-being and quality of life of breast cancer survivors in Negros Occidental. Likewise, it explored the relationship between psychological well-being and breast cancer survivors’ quality of life demographics such as age, educational attainment, years of survival, and living condition. A descriptive and correlational research design was used to assess breast cancer survivors’ psychological well-being and quality of life in Negros Occidental. Purposive sampling was utilized to come up with 43 respondents for this study. The research instrument used was Ryff’s (1989) Scale’s Psychological Well-Being and Flanagan’s (1982) Quality of Life Scale. Spearman Rank Correlation was used to determine the significant relationship between breast cancer survivors’ psychological well-being and quality of life. The study’s findings revealed that breast cancer survivors’ psychological well-being and quality of life are generally high. As to the relationship between psychological well-being and quality of life, the findings revealed a significant relationship between the two constructs; that is, when psychological well-being is very high, which means they have an excellent quality of life. This is to prove that breast cancer survivors are happy and able to function day to day.